Efficacy of plant volatiles for postharvest control of western flower thrips in fresh produce - van_Epenhuijsen, C.W.; Somerfield, K.G.; Hedderley, D. (New Zealand Plant Protection, 2008)
Insect infestation of fresh produce exported from New Zealand is an ongoing issue for exporters Seventeen lowhazard volatile compounds were screened for their potential as fumigants for controlling adults nymphs and eggs of western flower thrips (WFT) Frankliniella occidentalis (Pergande) WFT infested chrysanthemum flowers were exposed to volatiles in glass jars with circulation fans Higher mortality was achieved for adults than for nymphs/eggs Mortality after the 6 h exposure was greater than after the 2 h exposure Compounds that had good efficacy against WFT included 2propyn1ol diallyl sulphide (the main compound of garlic oils) 2methyl(E)butenal and ethyl acetate Of these 2propyn1ol caused significant phytotoxicity at the concentrations tested The other three were tolerated by the plant material and are worth further investigation